Evaluating Union Organising in the United Kingdom - Simms, Melanie; Holgate, Jane; Heery, Edmund (Warsaw Forum of Economic Sociology, 2013)
The paper evaluates the increasing focus on organizing activity within British trade union movement and its main purpose is to draw attention to the wider reasons why organizing is important. Contrary to a dominant the authors claim that organizing is more than simply recruiting members; it is about mobilizing members so that they have greater influence over their working lives. Outcomes of organizing campaigns can only be understood within a much broader evaluation of the purpose, strategies and context in which they take place. in the paper the authors evaluate the impact of the 'turn' to organizing in the United Kingdom trade union movement, especially after launching of the Organising Academy in 1998. While there are a lot of accomplishments resulting from organizing activities, they cannot overshadow less optimistic phenomena within the union movement such as stagnation in membership, failed attempts to reach new sectors of the economy, and worsening climate around organized labour since the outbreak of the financial crisis in 2008.